2021
DOI: 10.1002/cft2.20133
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of incorporated phosphorus fertilizer recommendations on no‐till managed winter wheat

Abstract: The current Oklahoma State University Soil, Water, and Forage Analytical Laboratory (OSU) phosphorus (P) recommendations were developed for conventional tillage systems with P fertilizer incorporated in the soil. The rate recommendations were based on a sufficiency approach, and included a pH adjustment factor. Increased adoption of no-till (NT) management across the region has resulted in more surface application of fertilizer, without concomitant changes in OSU recommendations. In the 2014-2015 and 2015-2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…As the depths approached the surface, the M3P values increased as well, detailing stratification in the nutrient availability. Relative yield across all data points ranged from 0.29 to 1.58, with only four of the seven locations responding to the addition of P fertilizer (data not shown) (Reed et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the depths approached the surface, the M3P values increased as well, detailing stratification in the nutrient availability. Relative yield across all data points ranged from 0.29 to 1.58, with only four of the seven locations responding to the addition of P fertilizer (data not shown) (Reed et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Not all treatments included in the trial were used in the analysis of this study, as some treatments were not yield limiting. Therefore, the treatments that were used for this study were all treatments from nonresponsive locations, and treatments that were at or above the rate that maximized yield in Reed et al (2021). These treatments were the 67 kg ha −1 at Red Rock 1, 56 kg ha −1 at Red Rock 2, and 34 kg ha −1 at Waukomis 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of response to P fertilizers under the low STP conditions at the N40 location has been reported by Reed et al . (2021) but the cause remains unknown. The limited responses to P fertilization in P-deficient soils are unique, as other studies have reported increases in yield by correcting P deficiencies (Bushong et al ., 2014; Chatterjee and Franzen, 2020).…”
Section: Discussionmentioning
confidence: 99%